SISTEM MANAJEMEN LINGKUNGAN, TRI HITA KARANA DAN IMPLEMENTASINYA PADA HOTEL - A. A. G. Raka Dalem (Environmental Research Center (PPLH) of Udayana University, 2008)
Environmental Management System (EMS) is very important in pursuing sustainable development. Problems were then arising, how to implement SML in the dimension of the Tri Hita Karana, Balinese life philosophy, so it is fit with Balinese life. Thus planning, doing, checking, actuating and controlling should be applied in the dimension of spiritual, socioeconomy (community) and environmental aspects, three aspects on the Tri Hita Karana philosophy. Because tourism is a major source of income for the Balinese it is then interesting to see how the EMS which adopt the THK philosophy being implemented in Bali. Many things can be learnt from its implementation on tourism sectors, especially on hotel businesses.